Resolution regarding the Government's attitude to the Beveridge Scheme - Cordon, R. H.
1943-03-10 1943 1940s 2 pages FALLOWFIELD DISCUSSION GROUP 28, Fallowfield, Cambridge. Tues. Mar. 10th. 1943. Dear Sir or Madam, An open air meeting called by the Fallowfield Estate Discussion Group in protest of the Government's attitude to the Beveridge Scheme, and in support of its immediate adoption passed the following resolution:- "This open air meeting of Fallowfield Residents believing that the immediate application of the Beveridge Scheme is necessary for winning the War, and winning a 'Freedom from Want' peace demand that the Government pass the scheme without delay''. It was agreed that copies of the resolution be sent to: The War Cabinet, The Leader of the House of Commons, The Leader of the Opposition, Sir William Beveridge, (with a covering letter), The National Council of Labour, The Trades Union Congress, The local Trades Council and Labour Party, the local Communist Party, the local Liberal Party, The local Conservative Association, all local branches of Trade Unions, The National Union of Railwaymen's Women's Gulid [Guild], The Associated Society of Locomotive Engineers and Firemen's Women's Society, The Cambridge Housewives' Association, The District Shop Stewards Council, The District Committee of the Amalgamated Engineering Union, The National Women's Parliament, the local Co-operative Party, The Bishop of Ely, The Vicar of St. Andrews, Chesterton, Cambridge, and the local Free Church Council. We should be glad if your organisation would pass a similar resolution, or take sympathetic action, and would be pleased to have your comments on our action. We may say that our Member of Parliament will be receiving a petition signed by the residents, when this has been completed. Yours faithfully, R.H. Cordon R.H. CORDON, Provisional Secretary. 292/150.5/5/95